Status of 174 Mhz RF system for BEP - Biryuchevsky, Yu.A.; Gorniker, E.I.; Kendjebulatov, E.K.; Krutikhin, S.A.; Kurkin, G.Ya.; Petrov, V.M.; Pilan, A.M. (Вопросы атомной науки и техники, 2012)
The new RF system for the BEP storage ring (which is an injector of VEPP-2000 accelerating complex) will increase the particles energy in the BEP from 0.9 to 1 GeV. RF system operates at a frequency of 174 MHz and consists of an accelerating cavity, RF power generator and control system.